Evaluation of the Significance of Tear Ferning Patterns in beta-Thalassemia Patients - Fagehi, Raied; Abbadi, Ibrahim M.; Abusharha, Ali; Alanazi, Mana A.; Malhan, Hafiz; El-Hiti, Gamal A.; Masmali, Ali M. (Klinische Monatsblätter für Augenheilkunde, 2021)
Aim This study was designed to evaluate the tear film in beta-thalassemia patients using tear ferning (TF) and phenol red thread (PRT) tests.Methods Forty beta-thalassemia patients, aged 18 – 38 years (25.7 ± 6.0 years), along with a control group of 40 age-matched subjects with healthy eyes completed the study. All subjects completed the ocular surface disease index (OSDI) first, followed by the TF and PRT tests with a 5-minute gap between the tests.Results Significant differences (Wilcoxon test, p < 0.05) were observed between the beta-thalassemia and control groups in all scores. Among beta-thalassemia patients, OSDI scores indicated eye dryness in 35 subjects (87.5%). PRT showed dryness in 31 subjects (77.5%) in the right and left eyes, and the TF grades were ≥ 2 for the tears collected from 35 subjects (87.5%). There was a strong correlation (r = 0.851, p = 0.001) between the PRT measurements in the right and left eyes. There was a medium correlation between OSDI and TF scores (r = 0.309, p = 0.026) and between OSDI and age (r = 0.365, p = 0.010). Age had a moderate negative correlation (r = − 0.328, p = 0.019) with the PRT obtained from the right eye.Conclusion Significant ocular dryness symptom was observed in beta-thalassemia patients, based on the scores collected from TF and PRT tests. Beta-thalassemia patients develop dry eyes, possibly due to several factors, including reduced tear secretion. Therefore, it is important to regularly evaluate both the quality and quantity of tears in patients with beta-thalassemia.
Keywords: dry eye; beta-thalassemia patients; phenol red thread test; dry eye questionnaire; tear film; five-point tear ferning grading scale